Indigenous Cultural Safety Trainings for Healthcare Professionals Working in Ontario, Canada: Context and Considerations for Healthcare Institutions - Denise Webb; Sterling Stutz; Claire Hiscock; Andrea Bowra; Tenzin Butsang; Sharon Tan; Bryanna Scott-Kay; Angela Mashford-Pringle (SAGE Publishing, 2023)
Background: Racism and discrimination are realities faced by Indigenous peoples navigating the healthcare system in Canada. Countless experiences of injustice, prejudice, and maltreatment calls for systemic action to redress professional practices of health care professionals and staff alike. Research points to Indigenous cultural safety training in healthcare systems to educate, train, and provide non-Indigenous trainees the necessary skills and knowledge to work with and alongside Indigenous peoples using cultural safe practices grounded in respect and empathy. Objective: We aim to inform the development and delivery of Indigenous cultural safety training within and across healthcare settings in the Canadian context, through repository of Indigenous cultural safety training examples, toolkits, and evaluations. Methods: An environmental scan of both gray (government and organization-issued) and academic literature is employed, following protocols developed by Shahid and Turin (2018). Synthesis: Indigenous cultural safety training and toolkits are collected and described according to similar and distinct characteristics and highlighting promising Indigenous cultural safety training practices for adoption by healthcare institutions and personnel. Gaps of the analysis are described, providing direction for future research. Final recommendations based on overall findings including key areas for consideration in Indigenous cultural safety training development and delivery. Conclusion: The findings uncover the potential of Indigenous cultural safety training to improve healthcare experiences of all Indigenous Peoples. With the information, healthcare institutions, professionals, researchers, and volunteers will be well equipped to support and promote their Indigenous cultural safety training development and delivery.